2003
DOI: 10.1046/j.1440-1754.2003.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Death due to electrocution in childhood and early adolescence

Abstract: Childhood deaths due to electrocution are rare and are more likely to occur when children are playing around electrical wires or equipment, and often result from either faulty apparatus, or a lack of understanding of the potential dangers involved. The majority of deaths (11/16; 69%) occur in the home environment. In contrast to adult electrical deaths, high-voltage electrocutions, suicides and workplace deaths are uncommon. Strategies for eliminating childhood electrocution should concentrate on ensuring safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
21
4
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 12 publications
13
21
4
4
Order By: Relevance
“…Our results differed from previous reports with rates of 54.5% in our population compared with 50% (Wright 1983), 12% (Fatovich 1992), 65.36% (Rautji 2003), and 32% (Karger 2002). We found deaths at home occurred in 45.5% of cases compared with 27%-69% in previous studies (Brokenshire et al 1984;Fatovich 1992;Karger et al 2002;Byard et al 2003;Rautji et al 2003).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results differed from previous reports with rates of 54.5% in our population compared with 50% (Wright 1983), 12% (Fatovich 1992), 65.36% (Rautji 2003), and 32% (Karger 2002). We found deaths at home occurred in 45.5% of cases compared with 27%-69% in previous studies (Brokenshire et al 1984;Fatovich 1992;Karger et al 2002;Byard et al 2003;Rautji et al 2003).…”
Section: Discussioncontrasting
confidence: 99%
“…In our study the cases were predominately 0-10 years, but in most previous studies the majority of the cases was in the 20-30 years age group. Similar to previous studies we found the upper extremity was the most common site involved (48%) (Gok and Soysal 1983;Erkol 1995;Byard et al 2003;Rautji et al 2003). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Banyo kŸveti i•ine •alÝßan sa• kurutma makinesi ile intihar eden (6), kaza sonucu šlen (4,13), baßarÝsÝz intihar girißimi sÝrasÝnda baßÝna defibrilatšr uygulayan saÛlÝk gšrevlisi, otoerotik aktivasyon saÛlamak amacÝyla elektrik uygulamalarÝ sÝrasÝnda hayatÝnÝ kaybeden ilgin• ve nadir olgular da bildirilmiß-tir (14,15). Üntihar olgularÝnÝn bŸyŸk kÝsmÝ dŸßŸk voltajlÝ elektrik akÝmÝ uygulamÝß olup (1,8,10,16,17) yŸksek akÝma maruz kalan olgular nadiren bildirilmißtir (15). Genel olarak yŸksek elektriksel gerilime maruz kalan elektrik šlŸmŸ olgularÝ sÝklÝkla kaza orijinlidir (1-3).…”
Section: Tartiþmaunclassified
“…Bildirilen olgular arasÝnda olgumuzdan farklÝ olarak hipnotik ila• alan vakalar bulunmaktadÝr (8,12), ancak olgumuzda olduÛu gibi depresif šzelliklerin bulunmasÝ šnemli bir bulgu olarak gšrŸlmektedir (8,9,16). Elektrik etkisine baÛlÝ šlŸmler sÝklÝkla kardiyak asistoli, ventrikŸler fibrilasyon, solunum kaslarÝnÝn tetanik kontraksiyonuna baÛlÝ solunum durmasÝ veya merkezi sinir sistemindeki solunum merkezi hasarÝna baÛlÝ gelißebileceÛi bildirilmektedir (1,3,17). OlgularÝn fiziksel incelemelerinde šzellikle yŸksek voltaja maruz kalan vakalarda aÛÝr yanÝklar, buna karßÝn dŸßŸk voltaja maruz kalanlarda hafif yanÝklar ile birlikte targetoid cilt lezyonlarÝ, keratin nodŸlleri izlenebilir (1,18).…”
Section: Tartiþmaunclassified